Direct numerical simulation of turbulent premixed ammonia and ammonia-hydrogen combustion under engine-relevant conditions. (5th March 2022) - Yang, W.; Ranga Dinesh, K.K.J.; Luo, K.H.; Thevenin, D.
Abstract: The combustion characteristics of ammonia and ammonia-hydrogen fuel blends under spark-ignited turbulent premixed engine-relevant conditions were investigated by means of direct numerical simulation and detailed chemistry. Several test cases were investigated for an outwardly expanding turbulent premixed flame configuration covering pure ammonia and ammonia-hydrogen fuel blends with 10% and 15% hydrogen content by volume for different equivalence ratio values of 0.9, 1.0 and 1.1. The results showed that the fuel-lean flames exhibit strong wrinkled structures at flame front compared to stoichiometric and fuel-rich flames. The heat release rate plots indicate that adding hydrogen into ammonia improves the reactivity of the flame and enhances the combustion process. The scatter plots of heat release rate versus local curvature coloured by NO formation, show that high heat release rate values occur in the concave structures and low heat release rate values occur in the convex structure, which is consistent with NO distribution. The highest turbulent burning velocity values were found for the fuel-lean cases due to more wrinkled flame front with lower effective Lewis number compared to fuel-rich cases. The results show a bending effect for the ratio between turbulent to laminar burning velocities with respect to hydrogen addition at all equivalence ratios with 10% hydrogen addition into ammonia exhibiting a highest value for the burning velocity ratio. Two distinct flame structures (concave and convex) were analysed in terms of local equivalence ratio based on the elements of N and O as well as H and O. They revealed an opposite distribution of NO formation normal to the flame front within concave and convex structures. Elementary chemical reactions involved in NO formation have shown that hydrogen addition into ammonia influences the reactivity of certain specific chemical reactions. Graphical abstract: Image 1 Highlights: Study of premixed ammonia and ammonia-hydrogen combustion at elevated pressures. Adding hydrogen into ammonia improves the reactivity of the flame. 10% hydrogen addition by volume into ammonia provides better flame conditions. NO formation is analysed.